Meningkatkan kinerja karyawan melalui Motivasi , Disiplin dan Sistem Kerja (HPWS) - Nugroho, Dedy (Fakultas Bisnis, 2024)
It is motivated by business competition in the fitness sector after the pandemic has ended, which has accelerated competency from moderate to higher competition and it is hoped that companies can face this problem. Therefore, it is necessary to increase employee performance which is able to encourage progress in various aspects of the fitness business, equipped with the HPWS (High Performance Work System) system which is also supported by work motivation and work discipline. This research aims to help maximize the company's potential to be able to compete and survive through employee performance, as well as finding out more about HPWS and the relationship between the influence of motivation and work discipline on employee performance. Research design, data and methodology: Using quantitative methods, data was collected and analyzed from 56 respondents who are Snap Fitness employees. This research used an online questionnaire by compiling question items to obtain a valid and reliable questionnaire with reference to previous research journals and analyzed using PLS (Partial Least Square) – SEM (Structural Equation Modeling). Results: The research results show that HPWS as a mediating variable has a role in helping companies improve employee performance. It is important for HPWS to be applied to companies to improve employee performance but not excessively so that it does not have a negative impact on employees and the organization, and factors must be taken into account. - factors that can influence so that the company's goals can be achieved optimally.